Defect engineering of metal halide perovskite optoelectronic devices. (September 2022) - Zhang, Xuanyu; Wang, Xiongbin; Liu, Huan; Chen, Rui
Abstract: Recently, thanks to their unique and attractive properties, such as tunable bandgap, high absorption coefficient, and long charge carrier diffusion length, metal halide perovskites have been recognized as one of the emerging candidates for next-generation optoelectronic devices. Optoelectronic devices based on perovskites have achieved significant breakthroughs in a relatively short period of time. However, their commercialization still faces various challenges, including stability, scalability, and reproducibility. Defects are often the culprits behind these problems, either inside the perovskites or at the device interfaces. Therefore, rational utilization of defect engineering to minimize the effect of defects on device performance and control of carrier behavior is the key to achieve efficient and stable perovskite-based optoelectronic devices (PODs). Given the important contribution to the rapid development of PODs, there is an urgent need to systematically investigate and summarize recent research advances in defect engineering. Therefore, in this review, defect physics in PODs are described in detail, the role and importance of defects in various PODs are highlighted, and various strategies for optimizing PODs are reviewed. Finally, based on the latest progresses and breakthroughs, the challenges facing in the future development of metal halide perovskites and their potential significance in the field of the optoelectronic are prospected.